Astragaloside IV promotes pharmacological effect of Descurainia sophia seeds on isoproterenol-induced cardiomyopathy in rats by synergistically modulating the myosin motor - Liu, Xingkai; Chen, Qian; Ji, Xuming; Yu, Wanchen; Wang, Tong; Han, Juanjuan; Li, Shumu; Liu, Jianan; Zeng, Fangang; Zhao, Yao; Zhang, Yanyan; Luo, Qun; et al. (Frontiers in Pharmacology, 2022)
Descurainia sophia seeds (DS), Astragalus mongholicus (AM), and their formulas are widely used to treat heart failure caused by various cardiac diseases in traditional Chinese medicine practice. However, the molecular mechanism of action of DS and AM has not been completely understood. Herein, we first used mass spectrometry coupled to UPLC to characterize the chemical components of DS and AM decoctions, then applied MS-based quantitative proteomic analysis to profile protein expression in the heart of rats with isoproterenol-induced cardiomyopathy (ISO-iCM) before and after treated with DS alone or combined with AM, astragaloside IV (AS4), calycosin-7-glucoside (C7G), and Astragalus polysaccharides (APS) from AM. We demonstrated for the first time that DS decoction alone could reverse the most of differentially expressed proteins in the heart of the rats with ISO-iCM, including the commonly recognized biomarkers natriuretic peptides (NPPA) of cardiomyopathy and sarcomeric myosin light chain 4 (MYL4), relieving ISO-iCM in rats, but AM did not pronouncedly improve the pharmacological efficiency of DS. Significantly, we revealed that AS4 remarkably promoted the pharmacological potency of DS by complementarily reversing myosin motor MYH6/7, and further downregulating NPPA and MYL4. In contrast, APS reduced the efficiency of DS due to upregulating NPPA and MYL4. These findings not only provide novel insights to better understanding in the combination principle of traditional Chinese medicine but also highlight the power of mass spectrometric proteomics strategy combined with conventional pathological approaches for the traditional medicine research.